Effect of a short-term water-based exercise program on cognitive skills in a Mexican older adult population - Canton-Martinez, Ermilo; Rentería, Iván; Machado Parra, Juan Pablo; Avilés-Reyes, Rubén; Hall-López, Javier Arturo; Ochoa-Martínez, Paulina Yesica; García Suárez, Patricia Concepción; Moncada-Jiménez, José; Johnson, David K.; Jiménez Maldonado, Alberto (Frontiers in Human Neuroscience, 2025)
IntroductionAging leads cognitive decline, affecting memory, attention, and executive functions. Physical exercise, particularly aerobic exercise, enhances cognitive function and health in older adults. Similarly, aquatic-based exercise improves cardiovascular fitness, muscle strength, and cognitive performance in acute- and long-term programs. The present study evaluated the effect of 4-week aquatic based exercise program on the cognitive function of older adults.MethodsSixteen older Mexican adults were assigned into an aquatic-based exercise (n = 9; 67.9 ± 6.9 years) or land-based exercise (n = 7; 66.8 ± 6.9 years) training groups. Verbal and visual memory were assessed via Rey Auditory Verbal Learning Test (RAVLT) and Rey Osterrieth Complex Figure test (ROCF). Executive functions for inhibitory control, cognitive flexibility, and verbal fluency were measured with the five-digit test (FDT) and the Controlled Oral Word Association Test (COWAT) respectively.ResultsEncoding and recall performance improved significantly following both interventions as recalled on RAVLT scores (p < 0.05). Favorable changes in visual memory were also observed for both groups with higher delayed recall scores once completed the exercise programs (p < 0.05). On the other hand, no significant changes in executive functions by either exercise intervention were observed.DiscussionAerobic exercise performed for 4 weeks may improve memory domains, regardless of the type of exercise practiced, while executive functions do not appear to be affected. The data obtained in the current work suggest that short-term interventions which involved aerobic exercise are feasible to improve the memory in older Mexican adults.